Pengaruh Atonik Terhadap Pertumbuhan Dan Produksi Tomat (Solanum lycopersicum L.) Varietas Servo - Feby Noor Budi M. W. A. K; Hamidah Hamidah; Suroto Suroto (Universitas Widya Gama Mahakam, 2019)
Atonic Effect on Growth and Production of Servo Varietal Tomatoes. The purpose of this study was to obtain the best atonic concentration on the growth and production of servo tomato varieties. This research was conducted for 5 months, starting from January to June 2018, starting from land preparation, planting, maintenance, harvesting to data collection. This research was conducted at Bumi Sempaja Blok A Housing, Sempaja Selatan Village, North Samarinda District. The study was arranged in a 5x1 Randomized Block Design and repeated 5 times. With treatment p0 (control), p1 (1 cc), p2 (2 cc), p3 (3 cc) and p4 (4 cc). The results of this study indicate that the atonic treatment has a very significant effect on the treatment of plant height, the number of flowers, the length of fruit to ripen, the number of fruits and production, but does not affect the duration of flower buds into fruit.